Covid-19 Infection on Asthma in an Immunocompromised Child: A Rare and Unusual Case - S Mouhdi; K El Fakiri; N Rada; G Draiss; M Bouskraoui (British Journal of Healthcare and Medical Research, 2023)
Introduction: Autoimmune lymphoproliferative syndrome is an immune system deficiency secondary to a disorder of lymphocyte homeostasis, the diagnosis of which is based on major and minor criteria. The combination of Asthma and COVID 19 has been described in numerous studies and several information has been disseminated on the presumed risk factors for COVID-19. Among these, the idea has emerged that people with autoimmune diseases have a higher risk of infection with COVID 19. The objective of our study is to assess the severity of COVID 19 infection in a patient with underlying pathologies. Observation: We report the case of an 8-year-old patient known to be asthmatic and followed for autoimmune lymphoproliferative syndrome since the age of 6 years. The patient presented to the Pediatric Infectious Diseases Department with exacerbation of asthma due to Covid-19 infection. She presented with wheezing dyspnea associated with fever and dry cough and was found to have febrile respiratory distress with wheezing rales on auscultation and signs of respiratory struggles requiring salbutamol nebulization. The evolution was marked by the improvement of dyspnea and cough with regression of fever after a therapy combining inhaled corticosteroids, antibiotics and hydroxychloroquine. Conclusion: This case study demonstrated that the occurrence of COVID 19 in an asthmatic and immunocompromised child was benign, and highlighted the dual benefit of hydroxychloroquine on COVID infection as well as on autoimmune lymphoproliferative syndrome.